Miao-Themed Souvenir Toys Design to Promote Tourism in Guizhou China - Jiangwei, Lu; Keai, Gregory Kiyai @ (South Asian Journal of Social Sciences and Humanities, 2024)
Purpose/Background: This study investigated the impact of Miao-themed souvenir toy design on promoting tourism in Guizhou, China. The culturally diverse province has an opportunity to leverage ethnic arts for tourism growth. Authentic representation of minority groups through creative mediums can attract visitor interest. Methods: A qualitative approach was used involving semi-structured interviews with Miao artisans who design souvenirs. Detailed interviews examined artistic processes and cultural representations in toys. Interview transcripts were analyzed using coding and thematic analysis. Findings: Interviews highlighted the cultural significance of toys for promoting both Miao heritage and local tourism. Artisans play a key role in authentically conveying minority culture through creative souvenirs. Culturally symbolic elements in toys resonate with tourists seeking an immersive experience. Conclusions: Findings demonstrate souvenir toy design as an avenue for boosting tourism while preserving ethnic arts in Guizhou. However, time limitations prevented thorough investigation of tourist preferences and trends influencing market success. Ongoing research is critically needed on optimizing cultural designs and effective promotion for visitor appeal.